The Economics of Has‐beens - MacDonald, Glenn; Weisbach, Michael S. (Journal of Political Economy, 2004)
The evolution of technology causes human capital to become obsolete. We study this phenomenon in an overlapping generations setting, assuming that technology evolves stochastically and that older workers find updating uneconomic. Experience and learning by doing may offer the old some income protection, but technology advance always turns them into has‐beens to some degree. We focus on the determinants (demand elasticities, persistence of technology change, etc.) of the severity of the has‐beens effect. It can be large, even leading to negatively sloped within‐occupation age‐earnings profiles and an occupation dominated by a few young, high‐income workers. Architecture displays the sort of features the theory identifies as magnifying the has‐beens effect, and both anecdotes and some data suggest that the has‐beens effect in architecture is extreme indeed.